WHICH IS SUPERIOR? COMPARATIVE STUDY OF HIGH SCHOOL AND VOCATIONAL SCHOOL IN ACCOUNTING MAJOR - Shafira Zahra Wirawan; Syihab Rifqi Hadzami; Azzahra Nabila; Faza Auliana Zein; Nurfajrina Oktadiani (Veteran Economics, Management, & Accounting Review, 2024)
Our research aims to determine and compare the influence of the school origin of students majoring in accounting on their understanding of accounting subjects when entering college. We used a qualitative research method with 3 methods of data collection, namely Zoom, voice recording, and direct interviews with 3 UPN "Veteran" Jakarta students in the 1st semester of the Bachelor of Accounting Program. Then the interview results are analyzed and attached descriptively. From these data, the author received the results that the school of origin influences the level of understanding of students' basic accounting concepts. Students from vocational schools have an advantage in facing accounting courses. However, this does not rule out the possibility of high school graduates surpassing vocational school graduates because what influences them most is their own encouragement.